Modelo de mensuração da competitividade da cadeia de valor no agronegócio - Santos, Jordana Rech Graciano dos (2020)
Brazil is located in Latin America, in a strategic region, close to other countries and of great territorial extension. In 2017, Brazil was the country with the best industrial performance in Latin America, and currently has an important pillar of the Gross Domestic Product (GDP), agribusiness representing about 21.4%. In order to maintain this growth and productivity levels, the agribusiness sector needs to invest in new technologies, innovation and research to remain competitive. In other words, having innovation processes that allow the quick identification of relevant stakeholder problems, in addition to managers sharing their view of the importance of needs or interests, in addition to the impact of potential problem solutions. Thus, this work has, as a general objective, the construction of a model for measuring the competitiveness of the value chain of the industrial sector of agribusiness. In this sense, in order to provide adequate guidance to companies, it is necessary to direct resources and strategic concepts to the development of new actions for modulation, delivery and capture of value in this sector. For the development of the diagnosis, the Performance Measurement System (SMD) is based on the concept of Key Performance Indicators (KPI), which were built based on the Critical Success Factors (FCS) and grouped into Fundamental Points of View (PVF) . The study took place in stages, through the theoretical construction of performance indicators, the use of the Delphi technique for validation with specialists, the MOORA method for correlation of factors and, finally, the application of the MAUT method (Multiattribute Utility Theory) for the weighting the importance of the mathematical model criteria. In total, the hierarchical structure had twenty-eight indicators, distributed among nine critical success factors and five fundamental points of view. The performance of six companies in the sector were analyzed in order to understand possibilities for improving the behavior of the analyzed indicators. The results indicate that the most important factors are the quality of the products and the efficiency of the processes, while the least important are collaboration and innovation. It emphasizes the importance of the sustainability factor, detected as a trend for the future, and the need to adapt companies to customers' needs. The research carried out is original and presents results consistent with the reality of the sector during the pandemic, where companies had different results.